2018
DOI: 10.3390/molecules23112781
|View full text |Cite
|
Sign up to set email alerts
|

Panax notoginseng Saponins Protect Cerebral Microvascular Endothelial Cells against Oxygen-Glucose Deprivation/Reperfusion-Induced Barrier Dysfunction via Activation of PI3K/Akt/Nrf2 Antioxidant Signaling Pathway

Abstract: Oxidative stress plays a critical role in cerebral ischemia/reperfusion (I/R)-induced blood-brain barrier (BBB) disruption. Panax notoginseng saponins (PNS) possess efficient antioxidant activity and have been used in the treatment of cerebral ischemic stroke in China. In this study, we determined the protective effects of PNS on BBB integrity and investigated the underlying mechanism in cerebral microvascular endothelial cells (bEnd.3) exposed to oxygen-glucose deprivation/reperfusion (OGD/R). MTT and LDH rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 58 publications
1
78
0
Order By: Relevance
“…Fortunately, both of them were notably upregulated with PNS intervention in spite of LPS challenge. Our previous investigation reveals that PNS promote the phosphorylation of Akt, which subsequently strengthen the nuclear Nrf2 activation and suppress the OGD/R-induced oxidative injury (Hu et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Fortunately, both of them were notably upregulated with PNS intervention in spite of LPS challenge. Our previous investigation reveals that PNS promote the phosphorylation of Akt, which subsequently strengthen the nuclear Nrf2 activation and suppress the OGD/R-induced oxidative injury (Hu et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, PNS treatment significantly upregulated Nrf2 activation, HO‐1 expression, and downregulated NF‐κB activation, regardless of LPS stimulation. Our prior study demonstrated that PNS acted as an efficient regulator that activated Nrf2/HO‐1 signaling depending on the PI3K/Akt pathway in OGD/R injured endothelial cells (Hu et al, ). Consequently, we likewise detected the level of Akt phosphorylation in this study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations